2019
DOI: 10.1111/imj.14148
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung abnormalities in the Queensland Lung Cancer Screening Study: prevalence and progression over 2 years of surveillance

Abstract: Background We report the prevalence and progression of incidentally detected interstitial lung abnormalities (ILA) in the Queensland Lung Cancer Screening Study cohort. Methods About 256 volunteers aged 60–74, with ≥30 pack years smoking history and forced expiratory volume in 1 s (FEV1) ≥50% predicted underwent low‐dose computed tomography (CT) chest screening. Electronic search of baseline (T0) and 2‐year follow‐up (T2) CT reports identified candidate cases using Fleischner Society interstitial terminology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 27 publications
2
17
2
Order By: Relevance
“…The prevalence of ILA in the present study is higher than other nonoccupational LDCT studies with reports ranging between 2.1% and 16.7% 41,44–48 and in LDCT studies of occupational (including asbestos) exposed populations the prevalence of ILA ranges from 0.7% to 25% 17,18 . Comparisons with other cohorts should be with care as standardized methods or criteria for describing ILA/ILD in CT populations have not been defined 49 .…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The prevalence of ILA in the present study is higher than other nonoccupational LDCT studies with reports ranging between 2.1% and 16.7% 41,44–48 and in LDCT studies of occupational (including asbestos) exposed populations the prevalence of ILA ranges from 0.7% to 25% 17,18 . Comparisons with other cohorts should be with care as standardized methods or criteria for describing ILA/ILD in CT populations have not been defined 49 .…”
Section: Discussioncontrasting
confidence: 56%
“…This is defined as specific radiologic, physiological, and histopathologic abnormalities in asymptomatic individuals or individual with ILA on CT imaging, which are usually more subtle than those of individuals with established disease 39 . The increasing use of chest CT both in clinical and research settings has increased the detection of subclinical ILD and the long‐term clinical significance of ILAs remain unclear 37–41 . Only a very small proportion (1.8%) in the present study of those with ILA fitted the accepted definition of declining pulmonary function in the context of ILD 14,36 and therefore there appears to be little role for antifibrotic therapy in this population.…”
Section: Discussionmentioning
confidence: 62%
“…In general population-based cohorts in which the mean age of participants with ILA was 70 years or older, the prevalence of ILA has been reported between 7 and 10% [ 8 , 16 , 17 ]. Among cohorts of smokers or lung cancer screening cohorts, however, the prevalence of ILA has been found to range from 4 to 20% [ 5 , 8 , 14 , 15 , 18–20 ]. While these numbers are similar to prevalence rates in the general population-based cohorts it should be noted that the mean age of participants with ILA in the cohorts of smokers ranged from 60 to 66 years, approximately 10 years younger than in the general population-based cohorts.…”
Section: Definition and Prevalence Of Interstitial Lung Abnormalitiesmentioning
confidence: 99%
“…Progression of ILA has been noted in 73–76% of participants with ILA over 5 years of follow up [ 50 , 74 ]. Still, studies with a follow up of 2 years, albeit with younger participants and a slightly differing definition of ILA, have found that a much lower proportion of participants progress over that time [ 14 , 18 ]. Progression to ILD has been found to be common among relatives of familial interstitial pneumonia patients with ILA [ 40 ].…”
Section: Progression Of Ilamentioning
confidence: 99%
“…Interstitial lung abnormalities (ILA) are a group of radiological findings visible on computed tomography (CT) of the lung in individuals without a diagnosis of interstitial lung disease (ILD) [1]. They are common in participants of lung cancer screening trials, patients with chronic obstructive pulmonary disease (COPD) and broad population-based cohorts [2][3][4][5][6][7][8]. Similar radiologic findings (nodular changes, reticulation, ground glass opacities and honeycombing) are also present in several interstitial lung diseases (ILDs), including idiopathic pulmonary fibrosis (IPF), and can precede onset of disease symptoms and diagnosis by several years [1,9,10].…”
Section: Introductionmentioning
confidence: 99%